Cognitive behavioral therapy for posttraumatic stress disorder in individuals with severe mental illness and borderline personality disorder. (March 2017) - Kredlow, M. Alexandra; Szuhany, Kristin L.; Lo, Stephen; Xie, Haiyi; Gottlieb, Jennifer D.; Rosenberg, Stanley D.; Mueser, Kim T.
Abstract: Secondary analyses were performed on data from two randomized controlled trials of a cognitive behavioral therapy (CBT) program for posttraumatic stress disorder (PTSD) in individuals with severe mental illness (SMI) to examine the feasibility, tolerability, and effectiveness for individuals with borderline personality disorder (BPD). In Study 1, 27 participants received CBT or treatment as usual. In Study 2, 55 participants received CBT or a Brief treatment. Feasibility and tolerability of CBT, PTSD symptoms, and other mental health and functional outcomes were examined, with assessments at baseline, post-treatment, and two follow-up time points. CBT was feasible and tolerable in this population. Study 1 participants in CBT improved significantly more in PTSD symptoms, depression, and self-reported physical health. Study 2 participants in both CBT and Brief improved significantly in PTSD symptoms, posttraumatic cognitions, depression, and overall functioning, with those in CBT acquiring significantly more PTSD knowledge, and having marginally significantly greater improvement in PTSD symptoms. CBT for PTSD was feasible and tolerated in individuals with SMI, BPD, and PTSD, and associated with improvements in PTSD symptoms and related outcomes. Prospective research is needed to evaluate CBT in individuals with BPD, including comparing it with staged interventions for this population. Highlights: PTSD in borderline personality disorder (BPD) can be treated effectively with CBT. CBT was feasible to provide and well tolerated by persons with severe BPD and PTSD. In 2 studies, CBT reduced PTSD symptoms more than in the control groups. Treatment benefits lasted for follow-up periods ranging from 6 to 12 months. PTSD can be treated with CBT in BPD patients without a stabilization phase.